Equal criminal investigation for all? An analysis based on the profile of victims of intentional homicides in Belém/Pará (Research, Society and Development, 2020)
Based on the principle of equality as a fundamental guarantee provided for in the Brazilian Federal Constitution and guiding the justice system, this work seeks to investigate the elucidation of police investigations into the crimes of murder that occurred in Belém/PA in the first semester of 2019, and correlating this with the profile of the victims of such crimes. The methodology used has a quantitative, descriptive and exploratory nature. This study aimes at characterizing the profile of the victims of the murders that occurred in the city of Belém/PA, from January to June 2019, regarding gender, age, skin color, education level, and location (neighborhood) of the crime. Our results suggest that the degree of vulnerability seems to indicate as an exclusion from the state interest in police investigations, with low rates of elucidation regarding the authorship of these crimes.